Do Cooperatives Exercise Market Power? Evidence from Pass-Through to Retail Prices - Federico M. Accursi; Raúl Bajo-Buenestado (CESifo GmbH, 2024)
Cooperatives, formally established to enhance social welfare and local economic development, often face pressures that divert them from these foundational goals and lead to their transformation into profit-driven entities that exploit market power. Leveraging an unexpected tax change following a vote of no confidence, we examine the pass-through to retail prices as a test for market power, using data from over 250 cooperatives operating in the Spanish fuel market. Our findings reveal a complete pass-through of the tax increase to retail prices. Additionally, descriptive evidence suggests that cooperatives consistently offer lower prices than their for-profit counterparts. These results are indicative of the absence of markup adjustments and market power exertion among cooperatives and are consistent with their prioritization of consumer welfare over profit maximization, thereby justifying the regulatory advantages they enjoy.
Keywords: D22; H22; H32; L21; L29; P13; 330; cooperatives; pass-through to prices; market power; firm conduct; retail fuel market